2014
DOI: 10.1093/jjco/hyu162
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of metastasis to mesorectal, internal iliac and obturator lymph nodes according to size criteria in patients with locally advanced lower rectal cancer

Abstract: Objective: This study was performed to clarify whether size criteria could be applied to the prediction of metastasis to the mesorectal, internal iliac and obturator lymph nodes in patients with lower rectal cancer. Methods: A total of 915 lymph nodes (416 mesorectal, 199 internal iliac and 300 obturator) from 53 patients with lower rectal cancer who underwent a curative resection were examined; 83 lymph nodes were positive. The sizes of the lymph nodes immediately after removal and those of paraffinembedded s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
(12 reference statements)
4
1
2
1
Order By: Relevance
“…7 mm. We previously reported that the sensitivity of detecting metastatic mesorectum lymph nodes was 90% when the cut-off value of the short axis diameter was set at 6.2 mm [14]. In that study, we confirmed that a short axis size of approximately 5 mm was sufficient to detect LPLN metastasis [14].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…7 mm. We previously reported that the sensitivity of detecting metastatic mesorectum lymph nodes was 90% when the cut-off value of the short axis diameter was set at 6.2 mm [14]. In that study, we confirmed that a short axis size of approximately 5 mm was sufficient to detect LPLN metastasis [14].…”
Section: Discussionsupporting
confidence: 79%
“…We reported that the optimal short axis cut-off value for determining the metastasis status in LPLN was ! 6 mm in the living body [12,14]. Based on our previous results, in this study, LPLNs larger than 6 mm in their short axis diameter in the MRI and MDCT images were diagnosed as positive of metastasis.…”
Section: Studysupporting
confidence: 54%
See 1 more Smart Citation
“…17 However, the PPVs in their study were below 20%, which were even lower than those estimated in our study for LLNs treated with CRT. 17 However, the PPVs in their study were below 20%, which were even lower than those estimated in our study for LLNs treated with CRT.…”
Section: Discussioncontrasting
confidence: 75%
“…Hatano et al reported that the PPVs of the sizes of resected LLNs were low compared to those of the mesorectal lymph nodes of patients treated with surgery alone without CRT. 17 However, the PPVs in their study were below 20%, which were even lower than those estimated in our study for LLNs treated with CRT. Therefore, the sizes of LLNs treated with CRT might be more diagnostically revealing than those of LLNs not treated with CRT.…”
Section: Discussioncontrasting
confidence: 75%